Strategi Pengembangan Bank Pembiayaan Rakyat Syariah di Indonesia - Anisa Dwi Utami; Lukman M Baga; Rahmat Yanuar; Tita Nursyamsiah; Busaid; Yekti Mahanani (Department of Islamic Economics, IPB University, 2023)
The business growth of Islamic rural Bank (BPRS) in Indonesia is higher than conventional rural bank, meanwhile it has the lower market share. One of the reasons could be the intense competition faced by Islamic rural banks with another islamic finance institution such as baitul maal wat tamwil (BMT) and islamic commercial banks which have also penetrated into the MSME segment. It makes islamic rural banks are often called having middle child syndrome, which have no speciality in facing the markets. This study aims to identify the strategy to develop and deep the market of islamic rural banks in Indonesia. This study was conducted using primary data through interview and focus group discussion (FGD) and SWOT. The methods used are business model canvass (BMC) and SWOT. The results of this study identified five key factors that play an important role in the development of the BPRS industry, namely 1) capital factor, 2) human resource (HR) factor, 3) information technology infrastructure factor, 4) business model, and 5) regulatory aspect.